Comportamiento agronómico y productivo de la línea promisoria de arroz (Oryza sp.) L-38 en la zona de Catarama, provincia los Ríos - Vera Valero, Melany Solange (2025)
Rice (Oryza sativa L.) is an important food crop worldwide, with a production exceeding 700 million tons. Rice breeding programs strive to address the need to constantly increase the crop's yield potential through various strategies. Given this situation, there is a need to identify new alternatives that can increase yields and improve grain quality. The promising L-38 rice line has shown great potential in other regions, but its performance under the specific conditions of the Catarama region is unknown. Therefore, the main objective of this study is to determine the agronomic and productive performance of the promising L-38 rice line in the Catarama region of Los Ríos province. A completely randomized block experimental design was used, applying the Tukey test with a 95% confidence level. To carry out the analysis, three replicates (three samples in areas of 4 m² carried out within a hectare of cultivation) and two varieties of cultivation (L-38 and SFL-11) were included. The data to be evaluated are: number of tillers per plant, plant height (cm), panicles per plant, panicle length (cm), number of grains per panicle, grain width (mm) with hull, grain length (mm) without hull, grain width (mm) without hull, yield (kg / ha), number of plants per hectare, planting spacing between plants, planting spacing between rows. As a result, the cultivar SFL-11 obtained a higher yield in km / ha achieved (4941.45) and the cultivar L-38 obtained a weight of (4482.87) km / ha. Finally, it was concluded that the promising line L-38 demonstrated higher profitability (78.00%) and a higher net benefit ratio (846.00) compared to the commercial cultivar SFL-11, which achieved a profitability of 22.00% and a net benefit ratio of 240.00.